A method for preparing high-density zirconium oxide ceramic microspheres

Through vacuum foam removal and multi-mesh spray head ball formation technology, combined with glue discharge, vegetative firing and self-grinding processes, the problem of insufficient density and sphericality of zirconia ceramic microspheres is solved, and the preparation of high-performance zirconia ceramic microspheres is realized.

CN115741991BActive Publication Date: 2025-05-02安徽致磨新材料科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111032454.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-03
Publication Date
2025-05-02
Estimated Expiration
2041-09-03

AI Technical Summary

Technical Problem

The existing zirconia ceramic microspheres have gaps in spherical shape and density, which limits their application in the field of high-end fine grinding.

Method used

The vacuum bubble removal device is used to reduce the bubbles in the slurry, and the slurry is pushed into the high-speed rotating liquid paraffin and solidify it. Then, the glue is discharged, vegetarian and self-grinding are carried out, and finally sintered at high temperature.

Benefits of technology

It improves the density and sphericality of zirconia ceramic microspheres, enhances its wear resistance, and meets the application needs of high-end fine grinding.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing high-density zirconium oxide ceramic microspheres, comprising the following steps: step 1: material preparation; step 5: adding zirconium oxide slurry into a syringe of a specific caliber, connecting a multi-mesh nozzle with a hose at the outlet of the syringe, pushing the slurry into high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 250-400r / min, the liquid paraffin water bath temperature is 50°C, the ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and undergo polymerization reaction in the liquid paraffin, and solidify into balls instantly; the invention uses the multi-mesh nozzle to push the slurry into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a certain speed, shortens the residence time of the slurry in the thrust device, prevents the reaction system from reacting in advance, and improves the utilization rate and production efficiency of the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of grinding medium preparation, in particular to a method for preparing high-density zirconia ceramic microspheres. Background Art

[0002] Zirconia ceramics are widely used in grinding materials due to their high strength and high wear resistance, especially as grinding media. According to incomplete statistics, the annual global consumption of grinding balls is as high as millions of tons, and my country accounts for more than half of the total consumption, so the market demand is huge. At the same time, with the development of science and technology, whether it is small molecule drugs in the pharmaceutical field or ultrafine powder coatings in the field of inks and coatings, higher requirements are put forward for the fineness of materials, which means that grinding media also put forward more stringent requirements, not only to meet the particle grading in the sense of size, but also to meet the use requirements of wear resistance, thus promoting the technical development of zirconia ceramic microspheres.

[0003] Developed countries such as Europe, America and Japan invested in the research and development of submillimeter ceramic microspheres early, and have now formed a considerable scale industry. In recent years, with the upgrading of domestic industries, attention has gradually been paid to the production and preparation of submillimeter ceramic microspheres, and a relatively mature industrial system has been formed. However, there is still a certain gap in the sphericity and density of submillimeter ceramic microspheres in the field of high-end fine grinding, which limits their application. Summary of the invention

[0004] To achieve the above object, the technical solution adopted by the present invention is:

[0005] A method for preparing high-density zirconium oxide ceramic microspheres comprises the following steps:

[0006] Step 1: Material preparation: prepare 3-6 portions of the required monomer acrylamide;

[0007] Cross-linking agent: N,N'-methylenebisacrylamide 0.3-3 parts;

[0008] 25-30 parts of deionized water;

[0009] Dispersant: 0.5-2 parts of sodium polyacrylate;

[0010] 60-70 parts of yttrium-stabilized zirconium oxide;

[0011] Initiator: ammonium persulfate 0.5-1.5 parts;

[0012] 1-3 parts of ammonia water;

[0013] Catalyst: 0.5-3 parts of tetramethylethylenediamine;

[0014] 200 parts of paraffin;

[0015] Step 2: Add acrylamide, N,N'-methylenebisacrylamide and ammonium polyacrylate into deionized water, stir electrically to obtain a solution, adjust the pH of the solution to 10-11 with aqueous ammonia, then add 3YSZ (3% yttria-stabilized zirconium oxide), stir electrically at high speed in a cold water bath at 17°C for 1-3 hours to obtain a zirconium oxide premix slurry;

[0016] Step 3: adding an initiator to the premixed slurry and stirring slowly for 15 minutes to obtain a reaction zirconia reaction slurry;

[0017] Step 4: The zirconium oxide reaction slurry is transferred into a vacuum defoaming device with stirring, and a small amount of defoaming agent is added dropwise to obtain a high solid content, low viscosity, uniform and bubble-free zirconium oxide slurry by vacuum defoaming;

[0018] Step 5: Add the zirconium oxide slurry into a syringe with a specific caliber. The outlet of the syringe is connected to a multi-mesh nozzle with a hose and pushed into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 250-400r / min. The temperature of the liquid paraffin water bath is 50°C. The ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and a polymerization reaction occurs in the liquid paraffin, solidifying into balls instantly.

[0019] Step 6: Take out the microsphere blank, stir it magnetically in 75% alcohol for 1-3 minutes, stir and clean it, and then wash it with clean water; after rinsing, dry it at 65°C to obtain the ceramic microsphere green body;

[0020] Step 7: Place the microspheres in an electric furnace and heat the temperature to 600°C at 1-5°C / min, then keep the temperature for 1-5 hours, and then heat the temperature to 1000°C at 0.5-7.5°C / min, and keep the temperature for 3 hours to obtain a zirconia ceramic microsphere blank;

[0021] Step 8: Put the zirconia ceramic microsphere blank into a planetary ball mill and grind it at 300-650 r / min for 1-8 hours to obtain a zirconia microsphere blank with good sphericity;

[0022] Step 9: Place the self-ground zirconia microsphere blank into a high-temperature electric furnace for firing. The firing system is: increase the temperature to 1000°C at 1-6°C / min, keep it warm for 3 hours, then increase the temperature to 1200°C at 0.5-7.5°C / min, keep it warm for 3 hours, and finally increase the temperature to 1550°C at 0.1-3°C / min, keep it warm for 3 hours to obtain high-performance zirconia ceramic microspheres.

[0023] Furthermore, in step 5, the high-speed rotating medium mixed with a certain proportion of catalyst is pushed in at a speed of 375 r / min.

[0024] Working principle and beneficial effects:

[0025] (1) The present invention utilizes a vacuum degassing device with stirring to vacuum degas the slurry, thereby reducing bubbles for subsequent ball forming and facilitating the densification of the green body.

[0026] (2) The present invention uses a multi-mesh nozzle to push the slurry into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a certain speed, thereby shortening the residence time of the slurry in the thrust device, preventing the reaction system from reacting prematurely, and improving the utilization rate of the slurry and production efficiency.

[0027] (3) The present invention performs debinding and bisque firing on the green body, and then performs self-grinding, which not only improves the strength of the green body, but also polishes the surface to improve the surface smoothness and sphericity; finally, after high-temperature firing, zirconia ceramic microspheres with high density and high sphericity are obtained, thereby obtaining good wear resistance. DETAILED DESCRIPTION

[0028] The present invention can be better understood with reference to the following examples. Example 1

[0029] A method for preparing high-density zirconium oxide ceramic microspheres comprises the following steps:

[0030] Step 1: Material preparation: prepare 3 parts of the required monomer acrylamide;

[0031] Cross-linking agent: 0.3 parts of N,N'-methylenebisacrylamide;

[0032] 25 parts of deionized water;

[0033] Dispersant: 0.5 parts of sodium polyacrylate;

[0034] 60 parts of yttrium-stabilized zirconium oxide;

[0035] Initiator: 0.5 parts of ammonium persulfate;

[0036] 1 part ammonia water;

[0037] Catalyst: 0.5 parts of tetramethylethylenediamine;

[0038] 200 parts of paraffin;

[0039] Step 2: Add acrylamide, N,N'-methylenebisacrylamide and ammonium polyacrylate to deionized water, stir electrically to obtain a solution, adjust the pH of the solution to 10-11 with aqueous ammonia, then add 3YSZ (3% yttria-stabilized zirconium oxide), stir electrically at high speed for 1 hour in a cold water bath at 17°C to obtain a zirconium oxide premix slurry;

[0040] Step 3: adding an initiator to the premixed slurry and stirring slowly for 15 minutes to obtain a reaction zirconia reaction slurry;

[0041] Step 4: The zirconium oxide reaction slurry is transferred into a vacuum defoaming device with stirring, and a small amount of defoaming agent is added dropwise to obtain a high solid content, low viscosity, uniform and bubble-free zirconium oxide slurry by vacuum defoaming;

[0042] Step 5: Add the zirconium oxide slurry into a syringe with a specific caliber. The outlet of the syringe is connected to a multi-mesh nozzle with a hose and pushed into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 250 / min. The temperature of the liquid paraffin water bath is 50°C. The ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and undergo polymerization reaction in the liquid paraffin, solidifying into balls instantly.

[0043] Step 6: Take out the microsphere blank, stir it magnetically in 75% alcohol for 1-3 minutes, stir and clean it, and then wash it with clean water; after rinsing, dry it at 65°C to obtain the ceramic microsphere green body;

[0044] Step 7: Place the microspheres in an electric furnace and heat the temperature to 600°C at 1°C / min, then keep the temperature for 1 hour, and then heat the temperature to 1000°C at 0.5°C / min, and keep the temperature for 3 hours to obtain a zirconia ceramic microsphere blank;

[0045] Step 8: Put the zirconia ceramic microsphere blank into a planetary ball mill and grind it at 300 r / min for 1 hour to obtain a zirconia microsphere blank with good sphericity;

[0046] Step 9: Place the self-ground zirconia microsphere blank into a high-temperature electric furnace for firing. The firing system is: increase the temperature to 1000°C at 1°C / min, keep it warm for 3 hours, then increase the temperature to 1200°C at 0.5 / min, keep it warm for 3 hours, and finally increase the temperature to 1550°C at 0.1°C / min, keep it warm for 3 hours to obtain high-performance zirconia ceramic microspheres. Example 2

[0047] A method for preparing high-density zirconium oxide ceramic microspheres comprises the following steps:

[0048] Step 1: Material preparation: prepare 6 parts of the required monomer acrylamide;

[0049] Cross-linking agent: 3 parts of N,N'-methylenebisacrylamide;

[0050] 30 parts of deionized water;

[0051] Dispersant: 2 parts of sodium polyacrylate;

[0052] 70 parts of yttrium-stabilized zirconium oxide;

[0053] Initiator: 1.5 parts of ammonium persulfate;

[0054] 3 parts of ammonia water;

[0055] Catalyst: 3 parts of tetramethylethylenediamine;

[0056] 200 parts of paraffin;

[0057] Step 2: Add acrylamide, N,N'-methylenebisacrylamide and ammonium polyacrylate to deionized water, stir electrically to obtain a solution, adjust the pH of the solution to 10-11 with aqueous ammonia, then add 3YSZ (3% yttria-stabilized zirconium oxide), stir electrically at high speed for 3 hours in a cold water bath at 17°C to obtain a zirconium oxide premix slurry;

[0058] Step 3: adding an initiator to the premixed slurry and stirring slowly for 15 minutes to obtain a reaction zirconia reaction slurry;

[0059] Step 4: The zirconium oxide reaction slurry is transferred into a vacuum defoaming device with stirring, and a small amount of defoaming agent is added dropwise to obtain a high solid content, low viscosity, uniform and bubble-free zirconium oxide slurry by vacuum defoaming;

[0060] Step 5: Add the zirconium oxide slurry into a syringe with a specific caliber. The outlet of the syringe is connected to a multi-mesh nozzle with a hose and pushed into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 400r / min. The temperature of the liquid paraffin water bath is 50°C. The ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and a polymerization reaction occurs in the liquid paraffin, solidifying into balls instantly.

[0061] Step 6: Take out the microsphere blank, stir it magnetically in 75% alcohol for 1-3 minutes, stir and clean it, and then wash it with clean water; after rinsing, dry it at 65°C to obtain the ceramic microsphere green body;

[0062] Step 7: Place the microspheres in an electric furnace and heat the temperature to 600°C at 5°C / min, then keep the temperature for 5 hours, and then heat the temperature to 1000°C at 7.5°C / min, and keep the temperature for 3 hours to obtain a zirconia ceramic microsphere blank;

[0063] Step 8: Place the zirconia ceramic microsphere blank in a planetary ball mill and grind it at 650 r / min for 8 hours to obtain a zirconia microsphere blank with good sphericity;

[0064] Step 9: Place the self-ground zirconia microsphere blank into a high-temperature electric furnace for firing. The firing system is: increase the temperature to 1000°C at 6°C / min, keep it warm for 3 hours, then increase the temperature to 1200°C at 7.5°C / min, keep it warm for 3 hours, and finally increase the temperature to 1550°C at 3°C / min, keep it warm for 3 hours to obtain high-performance zirconia ceramic microspheres. Example 3

[0065] The method for preparing high-density zirconium oxide ceramic microspheres comprises the following steps:

[0066] Step 1: Material preparation: prepare 4.5 parts of the required monomer acrylamide;

[0067] Cross-linking agent: 1.65 parts of N,N'-methylenebisacrylamide;

[0068] 27.5 parts of deionized water;

[0069] Dispersant: 1.25 parts of sodium polyacrylate;

[0070] 65 parts of yttrium-stabilized zirconium oxide;

[0071] Initiator: 1 part of ammonium persulfate;

[0072] 2 parts of ammonia water;

[0073] Catalyst: 1.75 parts of tetramethylethylenediamine;

[0074] 200 parts of paraffin;

[0075] Step 2: Add acrylamide, N,N'-methylenebisacrylamide and ammonium polyacrylate into deionized water, stir electrically to obtain a solution, adjust the pH of the solution to 10-11 with aqueous ammonia, then add 3YSZ (3% yttria-stabilized zirconium oxide), stir electrically at high speed for 2 hours in a cold water bath at 17°C to obtain a zirconium oxide premix slurry;

[0076] Step 3: adding an initiator to the premixed slurry and stirring slowly for 15 minutes to obtain a reaction zirconia reaction slurry;

[0077] Step 4: The zirconium oxide reaction slurry is transferred into a vacuum defoaming device with stirring, and a small amount of defoaming agent is added dropwise to obtain a high solid content, low viscosity, uniform and bubble-free zirconium oxide slurry by vacuum defoaming;

[0078] Step 5: Add the zirconium oxide slurry into a syringe with a specific caliber. The outlet of the syringe is connected to a multi-mesh nozzle with a hose and pushed into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 375 / min. The temperature of the liquid paraffin water bath is 50°C. The ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and undergo polymerization reaction in the liquid paraffin, solidifying into balls instantly.

[0079] Step 6: Take out the microsphere blank, stir it magnetically in 75% alcohol for 1-3 minutes, stir and clean it, and then wash it with clean water; after rinsing, dry it at 65°C to obtain the ceramic microsphere green body;

[0080] Step 7: Place the microspheres in an electric furnace and heat the temperature to 600°C at 2°C / min, then keep the temperature for 3 hours, and then heat the temperature to 1000°C at 1.5°C / min, and keep the temperature for 3 hours to obtain a zirconia ceramic microsphere blank;

[0081] Step 8: Put the zirconia ceramic microsphere blank into a planetary ball mill and grind it at 400 r / min for 3 hours to obtain a zirconia microsphere blank with good sphericity;

[0082] Step 9: Place the self-ground zirconia microsphere blank into a high-temperature electric furnace for firing. The firing schedule is: increase the temperature to 1000°C at 3°C / min, keep warm for 3 hours, then increase the temperature to 1200°C at 1.5 / min, keep warm for 3 hours, and finally increase the temperature to 1550°C at 1°C / min, keep warm for 3 hours to obtain high-performance zirconia ceramic microspheres.

[0083] Combining Example 1, Example 2 and Example 3: The present invention utilizes a vacuum degassing device with stirring to vacuum degas the slurry, thereby reducing bubbles for subsequent sphering and facilitating the densification of the green body; the present invention uses a multi-mesh nozzle to push the slurry into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a certain speed, thereby shortening the residence time of the slurry in the thrust device, preventing the reaction system from reacting prematurely, and improving the utilization rate of the slurry and the production efficiency; the present invention debinds and bisques the green body, and then performs self-grinding, which on the one hand improves the strength of the green body, and on the other hand polishes the surface to improve the surface smoothness and sphericity; finally, after high-temperature sintering, zirconia ceramic microspheres with high density and high sphericity are obtained, thereby obtaining good wear resistance.

Claims

1. A method for preparing high-density zirconium oxide ceramic microspheres, characterized in that The following steps are involved: Step 1: Material preparation: prepare 3-6 portions of the required monomer acrylamide; Cross-linking agent: N,N'-methylenebisacrylamide 0.3-3 parts; 25-30 parts of deionized water; Dispersant: 0.5-2 parts of sodium polyacrylate; 60-70 parts of yttrium-stabilized zirconium oxide; Initiator: ammonium persulfate 0.5-1.5 parts; 1-3 parts of ammonia water; Catalyst: 0.5-3 parts of tetramethylethylenediamine; 200 parts of paraffin; Step 2: Add acrylamide, N,N'-methylenebisacrylamide and ammonium polyacrylate into deionized water, stir electrically to obtain a solution, adjust the pH of the solution to 10-11 with ammonia water, then add 3YSZ, stir electrically at high speed for 1-3 hours in a 17°C cold water bath to obtain a zirconium oxide premix slurry; Step 3: adding an initiator to the premixed slurry and slowly stirring for 15 minutes to obtain a reaction zirconium oxide reaction slurry; Step 4: The zirconium oxide reaction slurry is transferred into a vacuum defoaming device with stirring, and a small amount of defoaming agent is added dropwise to obtain a high solid content, low viscosity, uniform and bubble-free zirconium oxide slurry by vacuum defoaming; Step 5: Add the zirconium oxide slurry into a syringe with a specific caliber. The outlet of the syringe is connected to a multi-mesh nozzle with a hose and pushed into the high-speed rotating liquid paraffin mixed with a certain proportion of catalyst at a speed of 250-400r / min. The temperature of the liquid paraffin water bath is 50°C. The ejected zirconium oxide slurry droplets automatically form balls under the action of centrifugal force, and a polymerization reaction occurs in the liquid paraffin, solidifying into balls instantly. Step 6: Take out the microsphere blank, stir it magnetically in 75% alcohol for 1-3 minutes, stir and clean it, and then wash it with clean water; after rinsing, dry it at 65°C to obtain the ceramic microsphere green body; Step 7: Place the microspheres in an electric furnace and heat the temperature to 600°C at 1-5°C / min, then keep the temperature for 1-5 hours, and then heat the temperature to 1000°C at 0.5-7.5°C / min, and keep the temperature for 3 hours to obtain a zirconia ceramic microsphere blank; Step 8: Place the zirconia ceramic microsphere blank in a planetary ball mill and grind it at 300-650 r / min for 1-8 hours to obtain a zirconia microsphere blank with good sphericity; Step 9: Place the self-ground zirconia microsphere blank into a high-temperature electric furnace for firing. The firing system is: increase the temperature to 1000°C at 1-6°C / min, keep it warm for 3 hours, then increase the temperature to 1200°C at 0.5-7.5°C / min, keep it warm for 3 hours, and finally increase the temperature to 1550°C at 0.1-3°C / min, keep it warm for 3 hours to obtain high-performance zirconia ceramic microspheres.

2. The method for preparing a high-density zirconia ceramic microsphere according to claim 1, characterized in that: In step 5, the high-speed rotating medium mixed with a certain proportion of catalyst is pushed in at a speed of 375 r / min.

Citation Information

Patent Citations

  • Alumina ceramic and preparation method thereof

    CN101117284A

  • Method for preparing zirconia ceramic microspheres

    CN110835263A